2003
DOI: 10.1073/pnas.2436518100
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific recombination by the DDE family member mobile element IS30transposase

Abstract: DNA rearrangements carried out by site-specific recombinases and transposases (Tpases) show striking similarities despite the wide spectrum of the catalytic mechanisms involved in the reactions. Here, we show that the bacterial insertion sequence (IS)30 element can act similarly to site-specific systems. We have developed an inversion system using IS30 Tpase and a viable phage, where the integration͞excision system is replaced with IS30. Both models have been proved to operate analogously to their natural coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…Furthermore, we noticed that the putative transposase of IS1237 contained the DDE motif (23). Recent research confirmed that a DDE family transposase is able to perform the functions of site-specific recombinases (22). Thus, it is possible that this transposase functions as a recombinase to catalyze the site-specific deletion of IS1237 in L. xyli subsp.…”
Section: Vol 189 2007 High-copy Is1237 Contains Bidirectional Promomentioning
confidence: 84%
“…Furthermore, we noticed that the putative transposase of IS1237 contained the DDE motif (23). Recent research confirmed that a DDE family transposase is able to perform the functions of site-specific recombinases (22). Thus, it is possible that this transposase functions as a recombinase to catalyze the site-specific deletion of IS1237 in L. xyli subsp.…”
Section: Vol 189 2007 High-copy Is1237 Contains Bidirectional Promomentioning
confidence: 84%
“…Chromosomal DNA was prepared from confluent cultures on brain heart infusion agar plates either by the hexadecyltrimethylammonium bromide extraction method as described previously (39) or with a QIAamp DNA minikit (QIAGEN Inc., Chatsworth, Calif.). Primers used for generating probes for hybridization, PCR, and nucleotide sequencing are listed in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…The orfA genes of IS605 and IS607 encode transposases belonging to two different families. IS607 orfA is predicted to encode a serine recombinase, most homologs of which catalyze only site-specific recombination (59), although one case in which this enzyme mediates both site-specific recombination and transposition has also been reported (39). In contrast, the IS605 orfA product is not considered to be a serine recombinase based on amino acid homologies.…”
mentioning
confidence: 99%
“…The founding member of the family, IS30, is the best characterized at the mechanistic level (117,(182)(183)(184)(185)(186)(187)(188)(189) and an in vitro transposition system has been developed (190). This 1,221 bp long Escherichia coli element belongs to a growing class of IS known to transpose through an intermediate formed by abutting the IR, donor primed transposon replication.…”
Section: (Iii) Mechanism and Insertion Specificitymentioning
confidence: 99%